A Smart Rubbish Bin Innovation (E.M.P.A.T.H.Y) for Household Organic Waste Management to Enhance Community Physical and Mental Well-being - Ramadhani Archam, Meuthia; Alfi Ghazali, Muhammad; Kayko Izzaki, Reyhan; Awwalurrohmah, Siti (Pelopor Publikasi Akademika, 2025)
One of the environmental problems in Indonesia is the waste management system that has not provided a solution for mountain runoff. Data based analysis from the 2023 national garbage treatment system, which was 69.9 million tons of garbage, was dominated by 41.60% leftover food garbage and 18,71% plastic garbage. From the source of the garbage, most garbage comes from households with about 44.37%. Indonesia's lack of awareness regarding the food waste, caused the tragedy of a garbage explosion that wiped out two villages with 143 people dead in 2005. The purpose of this idea is to expose the design of innovation, the design of smart rubbish bin E.M.P.A.T.H.Y. – Eco-friendly Machine Processing All Trash Holistically for You, as the solution to the processing of organic food waste. The method used in this study is a descriptive method. Where searches or data searches related to relevant topics on the Internet and this research is non-experimental. From the current environmental studies and literature case studies, the smart rubbish bin disposal solution is E.M.P.A.T.H.Y. – Eco-friendly Machine Processing All Trash Holistically for You, E.M.P.A.T.H.Y. – Eco-friendly Machine Processing All Trash Holistically for You It is equipped with the organic waste disposal features into environmentally friendly fertilizer, and it contains the responsible screen features to provide interactions to the user. The aim of the innovation of smart rubbish bin E.M.P.A.T.H.Y. can be used in the scale of homes, restaurants and public places like schools. The results of E.M.P.A.T.H.Y. product planning is expected to affect the public's awareness of waste removal. Sustained by the community's motivation to save the environment.